An Assessment of class teaching strategies among nursing students of Public & Private Nursing School of Sindh Province - Ahsanullah Qureshi', Pir Bux Jokhio2, Rashida Ahsan3, Moti Ram Bhatia , Gotum Kumar Jeswani , Rashid Hussain Burdi6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Introduction: The need of modern teaching methods and educational policies are considered vital in this era among nursing schools and educational centers in developing and developed countries for transferring of knowledge,skills, education and attitude to nursing students in order to achieve objectives of nursing curriculum for effective patient centered care. The survey was conducted for assessing of the knowledge of nursing students about effective teaching strategies for enhancements of students centered learning and later on teachers can adopt effective teaching and learning strategies. Objective: Present study was designed to assess the teacher's methodologies and strategies’ in nursing students of diploma and ascertain reasons for perceiving any teaching methods effective for diploma nursing students. Design of study: Cross-sectional study. Place & Duration: The study was conducted in Four Nursing schools of District Nawabshah two were private and two public from January to June 2017. Materials and Methods: For these study 100 students were selected through convince sampling and subdivided into four groups, 25 students were taken from each cluster in which 11 participants were dropped. Self-administered Questionnaire were distributed among targets students they were 37 male and 52 female (total 89) participated in the study; Each participant was individually explained purpose of the study and written consent was signed before hand covering questionnaire for study. Result: There is significant change was seen in interactive teaching session in teaching methodology about 999c of students were supported that strategy.Second1y,879a students participants were support in video learning, Thirdly 789c strongly agreed with relevant material provided during teaching as an effective teaching strategy. Conclusion: Interactive teaching session with provision of relevant material enhancing learning among nursting students, so interactive session along with material provided would useful strategies among nursing of schools of sindh.